2022
DOI: 10.21203/rs.3.rs-1809063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-adherence to WHO’s recommended antenatal care visits: Geospatial analysis of the 2017 Maternal Health Survey

Abstract: Introduction: Evidence shows that most women in Ghana do not meet the minimum antenatal care visits as recommended by WHO with only 31.2%-41.9% of them meeting the recommendation. To the best of our knowledge, no study in Ghana has examined women’s noncompliance with the WHO’s recommended eight antenatal visits using geospatial analysis, as this study sets out to do. Methods We sourced data from the recent version of the Ghana Maternal Health Survey which was executed in 2017. A sample of 10,077 women with c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Finally, the present study showed that men in rich category had lower likelihood of endorsing SSV. This is consistent with previous research, although such observations were found in both men and women [77]. When men can handle the financial burden of their families, they may experience fewer frustrations and irritations that often lead to perpetration of IPV [102,103].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Finally, the present study showed that men in rich category had lower likelihood of endorsing SSV. This is consistent with previous research, although such observations were found in both men and women [77]. When men can handle the financial burden of their families, they may experience fewer frustrations and irritations that often lead to perpetration of IPV [102,103].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, first, it was indicated that 36.5% of the women and 11.5% of men endorsed SSV in Zambia. This is consistent with prior studies within Zambia and other African countries that found women to be more likely to approve of IPV, including SSV, which was termed as "wife beating" [14,40,43,77]. Despite this, the lower prevalence rates of endorsing SSV among men should not be mistaken for decreased occurrences of SSV.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations